A selfie of academic research on games and gamification in Brazil: poses, scenarios and critical perspectives - Silva, Kleber Aparecido (The ESPecialist, 2022)
It is well known that the binomial games and gamification has been frequently used in academic literature in Applied Linguistics (GEE, 2004; SQUIRE, 2011; KAPP, 2012; LEFFA, 2014; QUADROS, 2016; LEFFA and VETROMILLE-CASTRO, 2019). In contrast, few studies proposed to present and discuss them in critical "poses" in and/or for language teaching (FINARDI et. al., 2019; ALEXANDRE and KOMESU, 2019; SILVA, 2019), thus aligning the results provided in and/or outside the classroom to (trans)train the pedagogical practices of language teachers in the 21st century. Given this gap in our field of research (LEFFA and VETROMILLE-CASTRO, 2019), we will seek in this article to provide conditions to take a selfie from the area, from different research scenarios, presenting, highlighting and discussing theoretical-methodological issues that have emerged in scientific studies conducted in the last decade in the Brazilian context. To meet these objectives, we made terminological and conceptual considerations about games and gamification in language teaching and, based on a specific time frame (2009-2019), we conducted a documental-critical research that, in addition to briefly punctuate the history of studies on games and gamification in language teaching in Brazil, discusses the research conducted at Master's and Doctorate levels focusing on this topic in its theoretical-methodological repercussions in qualified journals in the field. This premise will enable us to unveil new research horizons and will also enable us to draft proposals for a policy sensitive to educational demands, since this new teaching-learning context engenders specificities and, therefore, the language teacher needs to be prepared to act in this locus of learning.